The Effect of Using Literary Film to Improve Speaking Ability of the Tenth Grade Students at MA Al-Imaroh Wongsorejo - Roni Herlianto; Yuli Sugianto; Arin Inayah (LUNAR, 2019)
The thesis is about the effect of using literary film to improve speaking ability of the tenth grade student at MA Al Imarah Wongsorejo in the 2019/2020 academic year. The objective of this research is to know whether or not there is the effect of using literary film to improve speaking ability of the tenth grade student at MA Al Imarah Wongsorejo in the 2019/2020 academic year.The method used in this research is experimental quantitative method. The respondents of this research are 39 students of the tenth grade students. This research used purposive method to get the respondents of the research and the interview test to collect the data. The result of T- test is 13,420 and the T table value is 2,021 in the significant level 5% and degree of freedom was 37. It shows that the T-test value is higher than the value of T table. This data analysis is also strengthened by the average scores of students. The average score of the respondents’ posttest result was 73,974 which were higher than 39 in the experimental group that had gotten pretest. Based on the result of the data analysis and discussion, it can be concluded that, there is significant effect of literary film to improve speaking ability of Tenth Grade Students of MA Al Imarah Wongsorejo in 2019/2020 Academic year.